1990
DOI: 10.1007/bf01324298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social supports on attitudes, health behaviors and obtaining prenatal care

Abstract: The influence of social support on attitudes, health behaviors and attaining prenatal care was assessed in 300 postpartum patients. Demographic, medical, sociocultural, attitudinal and behavioral factors were assessed by interview and review of the medical chart. Three discrete social support factors (intimacy, comfort, security) were identified by factor analysis. The presence of social support was correlated with positive prenatal attitudes, not using drugs, and adequate health resources. Stepwise multiple-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 16 publications
1
17
0
2
Order By: Relevance
“…In addition, European-American women reported significantly higher levels of support from a romantic or marital partner than did African-American women. This echoes the findings of Giblin, Poland, and Ager (1990), who found lower levels of intimacy for black women than for white women. They also found that intimacy was associated with obtaining adequate prenatal care and other healthy behaviors.…”
supporting
confidence: 87%
“…In addition, European-American women reported significantly higher levels of support from a romantic or marital partner than did African-American women. This echoes the findings of Giblin, Poland, and Ager (1990), who found lower levels of intimacy for black women than for white women. They also found that intimacy was associated with obtaining adequate prenatal care and other healthy behaviors.…”
supporting
confidence: 87%
“…The positive influence of social attachments on participation in HPBs has been documented in recent studies on physical fitness (Reifman and Dunkel-Schetter, 1990) and on positive prenatal attitudes, not using drugs, and obtaining adequate health care (Giblin et al, 1990). Yarcheski and Mahon (I989) discovered that social support influenced participation in HPBs for both adolescents and adults but had the greater influence for adolescents.…”
Section: Hypothesesmentioning
confidence: 90%
“…Social support has been associated in some studies with earlier initiation of prenatal care (Giblin, Poland, & Ager, 1990;Schaffer & Lia-Hoagberg, 1997;Zambrana, Dunkel-Schetter, & Scrimshaw, 1996;Zambrana et al, 1997) and lower smoking (Schaffer & Lia-Hoagberg, 1997), alcohol (Stephens, 1985), or drug use (Giblin et al, 1990) during pregnancy. However, another study found no effect of social support on these pregnancy behaviors (Aaronson, 1989).…”
Section: Social Support and Pregnancymentioning
confidence: 99%